The Impact Of Brand Awareness, Brand Reputation, And Perceived Economic Benefits On Brand Trust And Online Purchase Intentions For Skintific Products On The Tiktok Shop Platform - TiffaErsantika Alhamdina, Tiffanda; Hartono, Arif (Publisher Cv. Inara, 2023)
This study aims to test and analyze the influence of brand awareness, brand reputation, perceived economic benefits on brand trust and online purchase intentions for Skintific products through the TikTok Shop platform. The research approach used is quantitative. Data collected by distributing online questionnaires via Google Form to 220 respondents. The sampling technique used convenience sampling method. The method used in this study is PLS-SEM, using the SmartPLS statistical software tool. Data analysis techniques used in this study are validity and reliability tests, collinearity tests, path coefficients, R-Square (R2), Q-Square, t-tests, and p-tests. The results of this study are brand awareness has a positive and significant effect on brand trust, brand awareness has no effect on online purchase intentions, brand reputation has a positive and significant effect on brand trust, brand trust has a positive and significant effect on online purchase intentions, perceived economic benefits have an effect positive and significant impact on brand trust, and perceived economic benefits have a positive and significant effect on online purchase intentions.